Enhanced IL-15-mediated NK cell activation and proliferation by an ADAM17 function-blocking antibody involves CD16A, CD137, and accessory cells - Jeffrey S Miller; Martin Felices; Shee Kwan Phung; Anders W Matson; Sam Wang; Ryan R Friess; Bruce Walcheck; Kate J Dixon; Jianming Wu; Rob Hullsiek; Anders J Lindstedt; Tanya S Freedman; et al. (Journal for ImmunoTherapy of Cancer)
Background Natural killer (NK) cells are being extensively studied as a cell therapy for cancer. These cells are activated by recognition of ligands and antigens on tumor cells. Cytokine therapies, such as IL-15, are also broadly used to stimulate endogenous and adoptively transferred NK cells in patients with cancer. These stimuli activate the membrane protease ADAM17, which cleaves various cell-surface receptors on NK cells as a negative feedback loop to limit their cytolytic function. ADAM17 inhibition can enhance IL-15-mediated NK cell proliferation in vitro and in vivo. In this study, we investigated the underlying mechanism of this process.Methods Peripheral blood mononuclear cells (PBMCs) or enriched NK cells from human peripheral blood, either unlabeled or labeled with a cell proliferation dye, were cultured for up to 7 days in the presence of rhIL-15±an ADAM17 function-blocking antibody. Different fully human versions of the antibody were generated; Medi-1 (IgG1), Medi-4 (IgG4), Medi-PGLALA, Medi-F(ab′)2, and TAB16 (anti-ADAM17 and anti-CD16 bispecific) to modulate CD16A binding. Flow cytometry was used to assess NK cell proliferation and phenotypic markers, immunoblotting to examine CD16A signaling, and IncuCyte-based live cell imaging to measure NK cell antitumor activity.Results The ADAM17 function-blocking monoclonal antibody (mAb) Medi-1 markedly increased early NK cell activation by IL-15. By using different engineered versions of the antibody, we demonstrate involvement by CD16A, an activating Fcγ receptor and well-described ADAM17 substrate. Hence, Medi-1 when bound to ADAM17 on NK cells is engaged by CD16A and blocks its shedding, inducing and prolonging its signaling. This process did not promote evident NK cell fratricide or dysfunction. Synergistic signaling by Medi-1 and IL-15 enhanced the upregulation of CD137 on CD16A+ NK cells and augmented their proliferation in the presence of PBMC accessory cells or an anti-CD137 agonistic mAb.Conclusions Our data reveal for the first time that CD16A and CD137 underpin Medi-1 enhancement of IL-15-driven NK cell activation and proliferation, respectively, with the latter requiring PBMC accessory cells. The use of Medi-1 represents a novel strategy to enhance IL-15-driven NK cell proliferation, and it may be of therapeutic importance by increasing the antitumor activity of NK cells in patients with cancer.